2019
DOI: 10.3390/ma12060949
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Albumin Encapsulated DNA Origami for Enhanced Cellular Transfection and Stability

Abstract: DNA nanostructures, owing to their controllable and adaptable nature, have been considered as highly attractive nanoplatforms for biomedical applications in recent years. However, their use in the biological environment has been restricted by low cellular transfection efficiency in mammalian cells, weak stability under physiological conditions, and endonuclease degradation. Herein, we demonstrate an effective approach to facilitate fast transfection of DNA nanostructures and enhance their stability by encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
(45 reference statements)
0
17
0
2
Order By: Relevance
“…4d) [47]. A similar effect was observed when using a chemically modified protein-cationic human serum albumin (HSA)-that is more biocompatible and easily available [48]. These investigations clearly demonstrated that decoration of DNA nanostructures with cationic polymers could be an efficient way to improve their physiological stability and modulate their in vitro and in vivo distribution.…”
Section: Polymer Modified Dna Nanomaterialsmentioning
confidence: 59%
“…4d) [47]. A similar effect was observed when using a chemically modified protein-cationic human serum albumin (HSA)-that is more biocompatible and easily available [48]. These investigations clearly demonstrated that decoration of DNA nanostructures with cationic polymers could be an efficient way to improve their physiological stability and modulate their in vitro and in vivo distribution.…”
Section: Polymer Modified Dna Nanomaterialsmentioning
confidence: 59%
“… 161–163 Xu et al coated DNA origami with cationic human serum albumin protein via electrostatic interaction. 163 The positive encapsulation was able to not only increase the transfection into HeLa cells by threefold, but also improve the stability of DNA origami under physiological conditions and from Deoxyribonuclease I (DNase I), a specific endonuclease commonly used to breakdown chromatin. A similar strategy was applied to coat dendrons of DNA origami with bovine serum albumin through cysteine-maleimide bond.…”
Section: Programmed Delivery Of Dna Nanostructuresmentioning
confidence: 99%
“…These hybrid systems can be extended to assemble multiple proteins, construct enzyme cascades and fabricate biosensors or biochips [ 82 , 83 ]. The generation of nucleic acid-protein conjugates is a promising and versatile tool to enhance gene delivery, modify the solubility, biological activity and stability of therapeutic cargos or the nanostructure [ 84 , 85 , 86 , 87 , 88 ]. As an unrivaled class of macromolecular drugs with high specificity, proteins are biodegradable, easily metabolized and amenable to surface modifications [ 89 ].…”
Section: Nucleic Acid Hybrid Nanocarriersmentioning
confidence: 99%